Mice deficient for the secreted glycoprotein SPARC/osteonectin/BM40 develop normally but show severe age-onset cataract formation and disruption of the lens. - Gilmour, D T (1998)
SPARC (secreted protein acidic and rich in cysteine, also known as osteonectin/BM40) is a secreted Ca2+-binding glycoprotein that interacts with a range of extracellular matrix molecules, including collagen IV. It is widely expressed during embryogenesis, and in vitro studies have suggested roles in the regulation of cell adhesion and proliferation, and in the modulation of cytokine activity. In order to analyse the function of this protein in vivo, the endogenous Sparc locus was disrupted by homologous recombination in murine embryonic stem cells. SPARC-deficient mice (Sparctm1Cam) appear normal and fertile until around 6 months of age, when they develop severe eye pathology characterized by cataract formation and rupture of the lens capsule. The first sign of lens pathology occurs in the equatorial bow region where vacuoles gradually form within differentiating epithelial cells and fibre cells. The lens capsule, however, shows no qualitative changes in the major basal lamina proteins laminin, collagen IV, perlecan or entactin. These mice are an excellent resource for further studies on how SPARC affects cell behaviour in vivo.